Optimal Exercise Prescription for Children and Adolescents with ADHD: A Narrative Review of Modality, Intensity and Dosage - Mokracka, Julia; Kręcina, Filip; Kaczmarek, Weronika; Fitz, Emilia; Brzeźniak, Mikołaj; Gil, Kacper; Daniek, Justyna; Drelich, Krzysztof; Karbowniczek, Aleksander; Grabarczyk, Alicja (Quality in Sport, 2026)
Background. ADHD is among the most common neurodevelopmental disorders in childhood, characterized by persistent inattention, hyperactivity, and impulsivity. While pharmacological treatment is effective, it is associated with adverse effects and limited efficacy for broader cognitive and motor difficulties. Physical activity has emerged as a promising adjunct, yet optimal exercise prescription parameters remain insufficiently defined. Aim. To synthesize evidence on the effects of different exercise modalities on cognitive, behavioral, and motor functioning in children and adolescents with ADHD. Material and methods. A literature search was conducted in PubMed and ScienceDirect (2016–2026). A total of 25 studies were included. Results. All examined exercise types demonstrated beneficial effects across ADHD-related outcomes, though with distinct profiles. Aerobic and closed-skill exercise most consistently reduced core ADHD symptoms including inattention (SMD = −1.51) and hyperactivity/impulsivity (SMD = −1.60). Open-skill activities produced the largest improvements in executive functions (SMD = 1.96) and inhibitory control (SMD = 1.94). Mind-body exercise significantly improved attention (SMD = −0.97) but showed limited evidence for broader executive or behavioral effects. HIIT and VR-based exercise represent promising emerging modalities. Regarding dosage, moderate-to-vigorous intensity and sessions of at least 60 minutes performed twice weekly were associated with the most robust outcomes. No single modality could be identified as definitively superior. Conclusions. Physical activity is a safe and clinically meaningful adjunct to ADHD treatment. An individualized approach guided by symptom profile and adherence is recommended. Future RCTs should establish precise exercise prescription guidelines for pediatric ADHD populations.